Plasma treatment of heat-resistant materials; Journal of Physics: Conference Series; Vol. 652 : Gas Discharge Plasmas and Their Applications (GDP 2015) - Vlasov V. A. Viktor Alekseevich; Kosmachev P. V.; Skripnikova N. K.; Bezukhov K. A. (2015, 2015)
Title screen